If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 + 5x = 100 Reorder the terms: 1 + 6x + 5x = 100 Combine like terms: 6x + 5x = 11x 1 + 11x = 100 Solving 1 + 11x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 11x = 100 + -1 Combine like terms: 1 + -1 = 0 0 + 11x = 100 + -1 11x = 100 + -1 Combine like terms: 100 + -1 = 99 11x = 99 Divide each side by '11'. x = 9 Simplifying x = 9
| 0=x^2+4x-11 | | 13x=8x-9 | | 4(5)-7(4)=-8 | | Z+2=17 | | 3.6(n+5.6)=14.4 | | x+6x=70 | | 4(x-18)=35+3x | | 31x+6=13x-2 | | 31x+6=13x-6 | | -2x+4x=0 | | 258=2x+6x-6 | | Xy+5y=x | | -6(x-2)=-6(x+2) | | 10x+10=15x-5 | | 1+k=-11+5k | | 11x+5=5x+15 | | -44=4z | | (7x+6)+(5x+3)=90 | | 7=3+k | | 74-60x=300 | | -2h=-18 | | 6+5x=-4x+57 | | c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 |